The persistence of caiçara culture in Perequê-Açú - Ubatuba-Brazil (Research, Society and Development, 2020)
This study discuss the production of space and territorialities at Perequê Açú beach, in the city of Ubatuba, on the northern coast of the state of São Paulo, with the objective to study socio-spatial and economic changes suffered by the traditional caiçara fishernan group. We opted for a method of ethnographic approach, of qualitative and exploratory research, with the application of direct interview with the main current leaders involved in the changes of the locality of Pereque-Açu, as well as tourists (90 interviewees) in the months of January and July 2019 and January 2020. The results indicated tourism activity as well as second-home real estate speculation in the context of maintaining Caiçara culture, which, being subjugated, moved to a peripheral area where it struggles for its survival without state support. The maintenance of the caiçara culture is necessary for the protection of this intangible heritage as well as for the survival of the local identity.